2020
DOI: 10.1002/ange.201916473
|View full text |Cite
|
Sign up to set email alerts
|

Grenzflächenpolymerisation: Von der Chemie zu funktionellen Materialien

Abstract: Abbildung 1. Chronologie der wichtigsten Entwicklungender Grenzflächenpolymerisation. Der untere (violette) Teil zeigt die wichtigenM eilensteine in der Polymerwissenschaft und der obere Teil die der Grenzflächenpolymerisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 258 publications
(268 reference statements)
0
1
0
Order By: Relevance
“…The initial decomposition temperature of the PAN/CFP/ZnO-Bi 2 O 3 nanofibrous membrane was about 206 °C. The increase in the initial decomposition temperature was probably influenced by the interfacial effect between ZnO-Bi 2 O 3 and PAN polymers (increase in interfacial size and chemical stability with temperature [45,46] ). The above study revealed that the PAN/CFP/ZnO-Bi 2 O 3 nanofibrous membrane was very stable below 206 °C and showed excellent thermal stability.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The initial decomposition temperature of the PAN/CFP/ZnO-Bi 2 O 3 nanofibrous membrane was about 206 °C. The increase in the initial decomposition temperature was probably influenced by the interfacial effect between ZnO-Bi 2 O 3 and PAN polymers (increase in interfacial size and chemical stability with temperature [45,46] ). The above study revealed that the PAN/CFP/ZnO-Bi 2 O 3 nanofibrous membrane was very stable below 206 °C and showed excellent thermal stability.…”
Section: Materials Characterizationmentioning
confidence: 99%